Airco Wind Turbine Prototype Design And Development - Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Ahmad, Mohd Nazri; Osman, Mohd Hairizal; Wahid, Mohammad Khalid; Mazlan, Siti Nur Humaira; Abdul Latiff, Muhammad (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The AIRco Wind Turbine is a new kind of product that can generate an electrical power from aerodynamic air flow that can be used to charge the phone. It is a green technology that used the wind as a source of energy to rotate the wind turbine and small electrical motor to generate an electrical power. This product is assembled and attached to the side of motorcycles basket in order to collect the wind energy to generate an electric power and also come with a gadget storage to place the phone when charging the battery. When travelling by riding the motorcycle, the energy from the aerodynamic air flow that occurs when increase the acceleration of the motorcycle can be converted to be an electrical power with adding few electrical components such as 12 volt DC electrical motor 5 volt voltage regulator and USB port which can used to charge our gadgets. It is an alternative way to generate the electrical power using the aerodynamic air flow as a free green energy. The objectives of this research are to analyze and propose the best blade design for wind flow, to design and develop functional prototype of AirCo Wind Turbine and to testing power generation from prototype.